2012
DOI: 10.1136/heartasia-2011-010079
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness contributes to coronary artery disease risk prediction beyond the traditional risk score (RAMA-EGAT score)

Abstract: ObjectivesThe traditional risk score (RAMA-EGAT) has been shown to be an accurate scoring system for predicting coronary artery disease (CAD). Arterial stiffness measured by the cardio–ankle vascular index (CAVI) is known to be a marker of atherosclerotic burden. A study was undertaken to determine whether CAVI improves the prediction of CAD beyond the RAMA-EGAT score.DesignCross-sectional study.PatientsPatients with a moderate to high risk for CAD by the RAMA-EGAT score were enrolled between November 2005 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 49 publications
2
49
0
8
Order By: Relevance
“…Several researchers reported that CAVI was high in patients with CAD [31,32,33]. Yingchoncharoen et al [34] reported that the traditional risk score (RAMA-EGAT) has been shown to be an accurate scoring system for predicting CAD. Furthermore, they reported that the addition of CAVI to the RAMA-EGAT score significantly improves the diagnostic yield of CAD.…”
Section: Cavi As a Surrogate Marker Of Arteriosclerotic Diseasesmentioning
confidence: 99%
“…Several researchers reported that CAVI was high in patients with CAD [31,32,33]. Yingchoncharoen et al [34] reported that the traditional risk score (RAMA-EGAT) has been shown to be an accurate scoring system for predicting CAD. Furthermore, they reported that the addition of CAVI to the RAMA-EGAT score significantly improves the diagnostic yield of CAD.…”
Section: Cavi As a Surrogate Marker Of Arteriosclerotic Diseasesmentioning
confidence: 99%
“…Several researchers reported that CAVI was high in patients with CAD 20,22,23) . Yingchoncharoen et al 24) reported that the traditional .…”
Section: Arteriosclerotic Diseases (A) Cadmentioning
confidence: 99%
“…Действительно, при изучении СЛСИ у больных ИБС достаточно убедительно показана его связь с рас-пространенностью коронарного атеросклероза [3,10,11]. Так, у больных сахарным диабетом 2-го типа СЛСИ позитивно коррелировал с кальциевым индек-сом коронарных артерий, определяемым при мульти-спиральной компьютерной томографии (r=0,303, p<0,0001) [10].…”
Section: Discussionunclassified
“…Так, у больных сахарным диабетом 2-го типа СЛСИ позитивно коррелировал с кальциевым индек-сом коронарных артерий, определяемым при мульти-спиральной компьютерной томографии (r=0,303, p<0,0001) [10]. Также есть свидетельства о наличии связи между СЛСИ и распространенностью [11] и выраженностью коронарного атеросклероза [6,9,12,13]. Так, при отсутствии стенозов КА СЛСИ составил 8,34±1,01, при стенозах одной, двух и трех КА -8,44±1,39; 9,95±1,22 и 10,12±1,56, соответственно, (р<0,05) [9].…”
Section: Discussionunclassified